Intestinal permeability and bacterial translocation in patients with liver disease, focusing on alcoholic aetiology: methods of assessment and therapeutic intervention. (October 2020) - Skinner, Charlotte; Thompson, Alex J.; Thursz, Mark R.; Marchesi, Julian R.; Vergis, Nikhil
Increased bacterial translocation (BT) across the gut barrier due to greater intestinal permeability (IP) is seen across a range of conditions, including alcohol-related liver disease (ArLD). The phenomenon of BT may contribute to both the pathogenesis and the development of complications in ArLD. There are a number of methods available to assess IP and in this review we look at their various advantages and limitations. The knowledge around BT and IP in ArLD is also reviewed, as well as the therapeutic strategies currently in use and in development.